Influence of land consolidation on soil characteristics and the technology of soil reconstruction - YE Yan-mei; WU Ci-fang (浙江大学学报. 农业与生命科学版, 2002)
It has been shown that farmland consolidation causes a big change of available phosphorus, available potassium and active organic matter in soil. Soil characteristics are different between digged soil and filled soil. Furthermore, different pattern and technology of farmland consolidation result in clear changes of soil characteristic. To ensure sustainable land use, the technology of soil reconstruction and methods of cultivation management are discussed in land consolidation area.